Biomedical Applications: A Bioprinted In Vitro Model for Osteoblast to Osteocyte Transformation by Changing Mechanical Properties of the ECM (Adv. Biosys. 10/2019). Issue 10 (15th October 2019) - Lee, Bryan E. J.; Shahin‐Shamsabadi, Alireza; Wong, Michael K.; Raha, Sandeep; Selvaganapathy, Ponnambalam Ravi; Grandfield, Kathryn
Abstract : In article number 1900126, Ponnambalam Ravi Selvaganapathy, Kathryn Grandfield, and co‐workers demonstrate the transformation of osteoblast‐like cells to osteocyte‐like cells by encapsulation in a bioprinted hydrogel matrix. This process mimics the natural phenotypical change osteoblasts undergo when encapsulated in bone matrix to become osteocytes. This in vitro model can be used for examining osteocyte interactions with drugs or interfacing biomaterials. Artistic credit: Lily Zhong.